Temperature Distribution Measurement on Combustion Chamber Surface of Diesel Engine - Experimental Method - SHIVA Kumar (International Journal of Automotive Science and Technology, 2017)
In case of petrol engine, the mixture of fuel and air in the correct ratio prepared in the carburetor entering into an engine cylinder during suction, but in case of the suction charge is only air from filter. Mixing of air and fuel in diesel engine takes place inside the cylinder at the end of compression.